ISSUES OF USING FINANCIAL RESOURCES TO ENSURE SUSTAINABLE DEVELOPMENT OF THE AGRICULTURAL SECTOR (International Journal of Innovative Technologies in Economy, 2025)
The agricultural sector is characterized by a number of specific features. First of all, reforms in this area are accompanied by instability of production. Many circumstances, such as climatic fluctuations, inflation rate, credit-price growth, decrease in purchasing power, significant reduction in state support for agriculture and the entire agro-industrial complex, increase in debts of agricultural producers and industrial enterprises producing means of production necessary for agriculture and agricultural producers, etc., affect the financial security of agricultural enterprises to one degree or another. In conditions of market relations, financial security, financial stability, financial security act as an important component for economically independent enterprises. Taking all this into account, the article approaches financing as the main condition for sustainable development of the agricultural sector. The author studies the experiences of Latvia, China, and Britain and makes proposals on financing directions to ensure sustainable development of the agricultural sector. The article analyzes the interaction of sustainable development and the agricultural sector, the needs arising from the goals of sustainable development, and argues that access to financial resources is a necessary condition for sustainable development. According to the author, sustainable development requires adequate financial support, and financing should be organized in accordance with the specialization of the agricultural sector, the characteristics of the region and the soil. In this case, it can be more efficient.